2023
DOI: 10.1146/annurev-pharmtox-051921-013755
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Ion Channels: What Are They Good For and Are They Druggable Targets?

Abstract: Lysosomes play fundamental roles in material digestion, cellular clearance, recycling, exocytosis, wound repair, Ca2+ signaling, nutrient signaling, and gene expression regulation. The organelle also serves as a hub for important signaling networks involving the mTOR and AKT kinases. Electrophysiological recording and molecular and structural studies in the past decade have uncovered several unique lysosomal ion channels and transporters, including TPCs, TMEM175, TRPMLs, CLN7, and CLC-7. They underlie the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 150 publications
0
18
0
Order By: Relevance
“…It has also been found that lysosomal membranes and ATP-dependent proton pumps keep the lumen acidic for enzyme activity [ 47 ]. However, lumen pH or lysosomal membrane permeability variations cause lysosome dysfunction, disrupting the autophagosome–lysosome fusion [ 48 ]. Changes in membrane permeability can produce acidification and necrosis.…”
Section: Effects Of Pesticides and Other Small Molecular Weight Envir...mentioning
confidence: 99%
“…It has also been found that lysosomal membranes and ATP-dependent proton pumps keep the lumen acidic for enzyme activity [ 47 ]. However, lumen pH or lysosomal membrane permeability variations cause lysosome dysfunction, disrupting the autophagosome–lysosome fusion [ 48 ]. Changes in membrane permeability can produce acidification and necrosis.…”
Section: Effects Of Pesticides and Other Small Molecular Weight Envir...mentioning
confidence: 99%
“…In eukaryotic cells, organelles orchestrate cellular homeostasis by integrating signalling and controlling the metabolic landscape (Julian & Stanford, 2020; Kat et al., 2022; Lawrence & Zoncu, 2019; Pfannschmidt et al., 2020; Savini et al., 2019; van Oosten‐Hawle & Morimoto, 2014; Yu & Yu, 2021; Zheng & Xiang, 2022). Ion channels, transporters and pumps support the selective passage of ions through the organellar membrane, providing a transmembrane drop in voltage that is used as a driving force for the transport of metabolites and byproducts of metabolic activity (Hille, 2001; Ishida et al., 2013; Jentsch et al., 2005; Palmieri, 2013; Riederer et al., 2023). Thus, the natural transit of chemical species through ion‐coupled facilitative transporters and/or the activation or inhibition of resident ion channels by signalling intermediates impacts the organellar membrane potential (Ψ org ) directly (Clapham & Ehrlich, 1996; Halestrap, 2013; Hayashi et al., 2006; Jain & Zoncu, 2022; Xu et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These have been implicated in various human pathological conditions associated with lysosomal storage diseases, such as neurodegenerative diseases, metabolic disorders and cancer (Ellison et al., 2023; Pfrieger, 2023; Shin et al., 2019; Toledano‐Zaragoza & Ledesma, 2020). Lysosomal storage diseases can arise from mutations in lysosomal enzymes, but naturally occurring variations in the expression and/or function of lysosomal ion channels and transporters can also lead to lysosomal storage diseases (Bissa et al., 2016; Cao et al., 2015; Feng et al., 2018; Huizing & Gahl, 2020; Kendall & Holian, 2021; Onyenwoke et al., 2015; Riederer et al., 2023; Shen et al., 2012; Zhang et al., 2018). Therefore, studying the electrophysiological properties of the lysosome and biophysics of ion transport systems in their native environment becomes crucial, because the establishment, maintenance and controlled changes in the membrane voltage are likely to play a fundamental physiological role.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations